2007
DOI: 10.1086/512241
|View full text |Cite
|
Sign up to set email alerts
|

Relapses ofPlasmodium vivaxInfection Usually Result from Activation of Heterologous Hypnozoites

Abstract: The P. vivax populations emerging from hypnozoites commonly differ from the populations that caused the acute episode. Activation of heterologous hypnozoite populations is the most common cause of first relapse in patients with vivax malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
272
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(291 citation statements)
references
References 27 publications
14
272
3
2
Order By: Relevance
“…This suggested that molecular methods could easily discriminate relapses, which would have the same genotype as the primary infection, from new infections, which would have a different genotype. This view has been challenged by the recent discovery of different parasite genotypes in primary infections and relapses in 72% of P. vivax-infected patients from Thailand, India and Myanmar (Imwong et al 2007b). Accurate detection of multiple-clone P. vivax infections becomes even more important in light of this report.…”
Section: Prevalence and Consequences Of Multiple-clone P Vivax Infecmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggested that molecular methods could easily discriminate relapses, which would have the same genotype as the primary infection, from new infections, which would have a different genotype. This view has been challenged by the recent discovery of different parasite genotypes in primary infections and relapses in 72% of P. vivax-infected patients from Thailand, India and Myanmar (Imwong et al 2007b). Accurate detection of multiple-clone P. vivax infections becomes even more important in light of this report.…”
Section: Prevalence and Consequences Of Multiple-clone P Vivax Infecmentioning
confidence: 97%
“…In general, multilocus analysis, such as microsatellite genotyping, detected greater numbers of multiple-clone infections when compared to single-locus analysis. The extensive clonal diversity of P. vivax infections in areas with relatively low malaria transmission, such as in Brazil and Colombia, is particularly surprising , Imwong et al 2007b). The only published comparison of microsatellite diversity in two human malaria parasite species co-circulating in the same area suggests that P. vivax infections comprise multiple clones (12 multiple-clone infections among 25 isolates typed) more often than P. falciparum infections (6 multiple-clone infections among 34 isolates typed) in rural Amazonia .…”
Section: Prevalence and Consequences Of Multiple-clone P Vivax Infecmentioning
confidence: 99%
“…This suggested that molecular methods could easily discriminate relapses, which would have the same genotype as the primary infection, from new infections, which would have a different genotype. This view has been challenged by the recent discovery of different parasite genotypes in primary infections and relapses for 72% of P. vivax-infected patients from Thailand, India and Myanmar (Imwong et al 2007b). Accurate detection of multiple-clone P. vivax infections is even more important in light of this report.…”
Section: Neutral or Nearly Neutral Molecular Markersmentioning
confidence: 99%
“…For example, in 90 P. vivax isolates from Thailand, Cui et al (2003b) found a multiple-clone infection rate of 25.6% using the PvCSP encoding gene alone, 19.3% using PvMSP-3α alone and 35.6% when the markers were combined. Particularly surprising is the extensive clonal diversity of P. vivax infections in areas with relatively low malaria transmission, such as Brazil, Colombia and Sri Lanka (Ferreira et al 2007, Imwong et al 2007b, Karunaweera et al 2008, Orjuela-Sánchez et al 2009a, Gunawardena et al 2010. The evolutionary and epidemiological consequences of multiple-clone P. vivax infections have not been well-investigated.…”
mentioning
confidence: 99%
“…A variety of methodologies have been developed for P. vivax with as few as three polymorphic markers proving to be sufficient to discriminate homologous from heterologous infections. [73][74][75][76] However, recurrence of P. vivax genetically identical to the pretreatment isolate can occur from either a true recrudescence of the initial infection or a relapse from hypnozoites generated from the prior blood-stage infection 74,77 ; unsurprisingly molecular methods are unable to distinguish between these alternatives. Relapses are also commonly genetically heterologous.…”
mentioning
confidence: 99%